Erratum: Treatment and Classification of Nevus of Ota: A Seven-Year Review of a Single Institution's Experience - Nam, Jae-Hui; Kim, Han-Saem; Choi, Young Jun; Jung, Ho Joo; Kim, Won-Serk (Annals of dermatology, 2017)
[This corrects the article on p. 446 in vol. 29, PMID: 28761293.].